2019
DOI: 10.1002/jat.3780
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury model established by systemic glutathione depletion in mice

Abstract: Glutathione (GSH) is one of the most extensively studied tripeptides. The roles for GSH in redox signaling, detoxification of xenobiotics and antioxidant defense have been investigated. A drug‐induced rhabdomyolysis mouse model was recently established in L‐buthionine‐(S,R)‐sulfoximine (BSO; a GSH synthesis inhibitor)‐treated normal mice by co‐administration of antibacterial drug and statin. In these models, mild kidney injury was observed in the BSO only‐treated mice. Therefore, in this study, we studied kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The maintenance of hemodynamic stability needs to be given extensive consideration in AKI because of the impaired autoregulation mechanisms that are present ( Ostermann et al, 2019 ). As previously stated, RG has the potential to attenuate the damaging peroxide metabolites, decrease oxidative stress, and perform specific metabolic functions in the production of inflammatory components ( Matsubara et al, 2019 ; Zhang and Bai, 2019 ; Wang and Wu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of hemodynamic stability needs to be given extensive consideration in AKI because of the impaired autoregulation mechanisms that are present ( Ostermann et al, 2019 ). As previously stated, RG has the potential to attenuate the damaging peroxide metabolites, decrease oxidative stress, and perform specific metabolic functions in the production of inflammatory components ( Matsubara et al, 2019 ; Zhang and Bai, 2019 ; Wang and Wu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previously single-center clinical studies indicated Chuan Huang Fang (CHF) might have nephroprotection in A on C patients via mechanisms of reducing oxidative damage and decreasing inflammatory reactions ( Gong et al, 2014 ; Gong et al, 2020 ; Gong et al, 2021 ). Reduced glutathione (RG) has been shown to be beneficial in controlling local inflammation, reducing accumulation of reactive oxygen species, decreasing inflammatory markers, and lowering oxidative stress in the tissues and organs ( Matsubara et al, 2019 ; Zhang and Bai, 2019 ; Wang and Wu, 2021 ). Recently, it has been ascertained that RG could increase the therapeutic efficacy of high-flux hemodialysis among patients with severe AKI ( Hu, 2015 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of autoregulation mechanisms damaged in AKI, maintaining hemodynamic stabilization should be attached great significance to [ 49 ]. As stated above, RG could clear away the harmful peroxide metabolites, restrain oxidative stress, and play certain metabolic roles in inflammatory factors [ 29 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of AKI, numerous oxygen-free radicals are generated, endogenous antioxidants are constantly consumed, and large numbers of inflammatory factors are released, aggravating kidney injury [ 28 ]. Reduced glutathione (RG) can effectively control the local inflammatory response, reduce the accumulation of reactive oxygen species in renal tissues, lower the level of inflammatory factors, and relieve oxidative stress in organs and tissues [ 29 – 31 ]. Recently, RG is reported to improve the clinical efficacy of HFHD in patients with severe AKI [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione is a powerful antioxidant whose activity decreases with protein restriction. Lower glutathione levels are associated with greater reperfusion injury in AKI in animal models and humans (32)(33)(34), and glutathione suppresses prostaglandin synthesis pathways (35,36). In addition, glutathione plays a role in regulating cholesterol.…”
Section: Discussionmentioning
confidence: 99%